2014
DOI: 10.1186/1756-0500-7-564
|View full text |Cite
|
Sign up to set email alerts
|

High carbohydrate diet and physical inactivity associated with central obesity among premenopausal housewives in Sri Lanka

Abstract: BackgroundPrevalence of obesity and overweight is rising in developing countries, including Sri Lanka at a rapid pace due to dietary and lifestyle changes. This study aimed to assess the association between high carbohydrate diet, physical inactivity and central obesity among premenopausal housewives in Sri Lanka.MethodsThis study was conducted as a cross-sectional study. A sample of 100 premenopausal women with home duties aged between 20 to 45 years were selected randomly from two divisional secretariats (DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
1
10
1
2
Order By: Relevance
“…The mean BMI of women was higher than that of the men which is similar to previous studies [44,45,47]. The mean WC of women (85.96 [9.53] cm) was higher than the Asian cut-off and previously reported values by Katulanda et al (76.8 [12.2] [49]. The average WC for men (84.79 [9.38] cm) was less than the Asian cut-off, but higher than previously reported values.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The mean BMI of women was higher than that of the men which is similar to previous studies [44,45,47]. The mean WC of women (85.96 [9.53] cm) was higher than the Asian cut-off and previously reported values by Katulanda et al (76.8 [12.2] [49]. The average WC for men (84.79 [9.38] cm) was less than the Asian cut-off, but higher than previously reported values.…”
Section: Discussionsupporting
confidence: 89%
“…The mean BMI for men in the present study is similar to the average BMI for men reported using national (21.1 [3.7] kg/m 2 ) [8], provincial (Central Province, 22.7 [4.2] kg/m 2 [46]; four provinces, 21.5 [3.7] kg/m 2 [47]) and district (Colombo district, 22.8 [4.3] kg/m 2 [48]; Kaluthara district, 21.9 [0.46] kg/m 2 [45]) populations. Rathnayake et al [49] reported a higher average BMI for adult women than in our present study; conversely, the average BMI for women reported by Katulanda et al [8] (22.7 [4.5] kg/m 2 ) was lower than the current study. However, an average BMI for women similar to the present study has also been reported [45,47,48].…”
Section: Discussioncontrasting
confidence: 89%
“…Beyond the lack of absolute or relative measures of validity, reliability, or feasibility of some PSEEs 28 , 29 , 42 , 43 , 54 , 58 , 62 , 63 , 77 , 79 or the only partial validation of other PSEEs, 33 , 41 , 53 , 59 , 66 , 68 , 83 other limitations included the following: low sensitivity of the tool due to a small number of portion options or photos 11 , 17 , 25 , 26 , 29 , 32 , 40 , 43 , 52 , 55 , 65 ; grouping of mixed dishes and omission of food items in questionnaires 27 , 35 , 42 ; lack of breadth 28 ; requirement for high level of staff training or involvement 33 , 37 , 64 , 68 ; requirement for participants to be literate or skilled in operating equipment 33 , 37 or in performing numerical calculations 30 ; requirement for participants to possess specific technology 29 ; long time elapsed between dietary assessment with the new PSEE and the comparison method (which effectively means the 2 methods were comparing different things), or long time elapsed between test and re-test evaluations 26 , 38 , 40 ; and testing of PSEE in only one gender or age group 17 , 25 , 30–32 , 36–38 , 55 , 56 , 61 , 63 , 64 , 83 , 79 . Other issues were validation conducted in nonminority ethnic group populations 30 , 41 ; low retention rates 41 , 43 ; study not powered to detect ethnic subgroup differences 29 or validity/reliability 38 , …”
Section: Resultsmentioning
confidence: 99%
“…At present, carbohydrates constitute the majority of the energy intake among South Asian countries such as Sri Lanka (~71.2%) [32]; in contrast, the consumption of carbohydrates is lower in Western countries (~45%) [33]. Furthermore, high carbohydrate intake has been associated with an increased risk of diabetes in a South Indian population [34] and an increase in WC among premenopausal (20-45 years) Sri Lankan women [35]. In the present study, we found a significant interaction between the metabolic-GRS and carbohydrate energy percentage on waist-to-hip ratio, where the individuals carrying more than nine risk alleles had a higher waist-to-hip ratio among those in the highest tertile of carbohydrate energy percentage.…”
Section: Discussionmentioning
confidence: 99%